BIOACTIVE PEPTIDES DERIVED FROM FISH AND FISH WASTE ANDITS POTENTIAL APPLICATION ON HUMAN HEALTH: A MINI REVIEW - VAISHNAV, ANAND; MEHTA, NARESH KUMAR; PRIYADARSHINI, M. BHARGAVI; LAL, JHAM; SINGH, N. SURESHCHANDRA; PATI, BIKASH KUMAR (Journal of the Inland Fisheries Society of India, 2026)
A bioactive peptide consists of food derived constituents containing 2 to 20 amino acids linked with an amide or peptides bond and have physiological consequences in human body (Gaikwad et al., 2021). Bioactive peptides are absorbed into the human body through the small intestine, after which these biopeptides enter inside the circulatory system to exert a variety of physiological consequences or cause some minor effects in the digestive system (Ortizo et al., 2021).